Interview about PAVIVIS: Program to Support Victims of Sexual Violence - Martins, Margarita (Guará Journal, 2025)
Created in 1998, the Sexual Violence Victims Assistance Program (pAvIvIS) is now a benchmark in the sector. Through the program, more than four thousand children and women who are victims of this type of violence have been assisted and referred. The program is also responsible for referring cases to legal authorities, becoming the only reference for legal abortion. Operating with a limited number of professionals and in a borrowed space at the Health Sciences Center, pAvIvIS is now seeking new impetus to continue providing the important services it provides to the people of Espírito Santo.